UJI AKTIVITAS ANTIBAKTERI MADU HITAM PAHIT DALAM MENGHAMBAT PERTUMBUHAN BAKTERI Esherichia coli DI LABORATORIUM ANALIS KESEHATAN POLITEKNIK PIKSI GANESHA BANDUNG - Ria Khoirunnisa Apriyani; Sindi Cantika (INFOKES (Informasi Kesehatan), 2021)
This study aims to determine the antibacterial activity of bitter black honey in inhibiting the growth of Escherichia coli and also to determine the highest concentration of bitter black honey which has the greatest inhibition zone in inhibiting the growth of Escherichia coli. This study used a descriptive experimental method and a Completely Randomized Design. This activity test used the Kirby-Bauer diffusion technique with a bacterial cell count of 10-8 CFU/ml. The test was carried out using bitter black honey with various concentrations of 20%, 40%, 60%, 80% and 100%, positive control used gentamicin antibiotic, while negative control used sterile distilled water and the test was carried out in 3 repetitions. The results showed that the bitter black honey had antibacterial activity at all concentrations from 20%, 40%, 60%, 80%, until 100% in inhibiting the growth of Escherichia coli with the weak to strong category, namely 3,3 mm – 7,3 mm. While the largest concentration of bitter black honey was at a concentration of 100% with an average inhibition zone of 7,3 mm and was in the medium category.